Drivers of a riparian forest specialist (Carex remota, Cyperaceae): It is not only a matter of soil moisture1. Issue 8 (1st August 2014) - Uria‐Diez, Jaime; Gazol, Antonio; Ibáñez, Ricardo
Abstract : Premise of the study: Plants respond to the prevailing conditions in the surrounding environment, but since they are dynamic systems this response may vary during their life. Thus, the identification of key aspects for the maintenance of plant populations requires the consideration of plant performance across environmental gradients and along life stages. This study examines how abiotic conditions and biotic interactions and processes determine the spatial distribution of two life‐story stages that play a key role in the functioning of a representative population of Carex remota . Methods: We used structural equation modeling (SEM) to test for direct and indirect influences of abiotic and biotic factors on seedlings and adults of Carex remota . The variables used in the analysis were number of seedlings, cover of adults, soil moisture, leaf litter cover, relative light, and topographic position. Key results: Population patterns partially depend on direct and indirect effects of abiotic conditions. Whereas adult individuals were only affected by topsoil moisture, seedling emergence was largely affected by multiple environmental conditions. The number of seedlings increased with high topsoil moisture, low leaf‐litter values, high light values as well as in low parts of the study area. The importance of adult individuals in determining seedling success is also highlighted: higher abundance provides seed rain in the surroundings and modifies the microenvironmental conditions favoring high seedling establishment. Conclusions: As hypothesized, adults and seedlings responded to the environmental conditions differently. Seedling emergence was a critical aspect in C. remota performance, and abrupt changes in the environment during this stage may strongly influence population performance.